Adjunctive probiotic microorganisms to prevent rehospitalization in patients with acute mania: A randomized controlled trial. (25th April 2018) - Dickerson, Faith; Adamos, Maria; Katsafanas, Emily; Khushalani, Sunil; Origoni, Andrea; Savage, Christina; Schweinfurth, Lucy; Stallings, Cassie; Sweeney, Kevin; Goga, Joshana; Yolken, Robert H
Abstract : Objective: Immunological abnormalities play a role in the pathophysiology of mania and have been associated with relapse. Probiotic organisms such as Lactobacilli and Bifidobacteria modulate inflammation in humans and animal models. The trial examined whether the administration of probiotic organisms prevents psychiatric rehospitalizations in patients recently discharged following hospitalization for mania. Methods: Patients hospitalized for mania (N = 66) were randomized after discharge to receive 24 weeks of adjunctive probiotics ( Lactobacillus rhamnosus strain GG and Bifidobacterium animalis subsp. lactis strain Bb12) or adjunctive placebo in a parallel two‐group design format. The effect of treatment group on the risk of rehospitalization was calculated using Cox regression models. The modulating effect of systemic inflammation was measured employing an inflammation score based on immunoglobulin levels directed at previously defined antigens. Results: During the 24‐week observation period there were a total of 24 rehospitalizations in the 33 individuals who received placebo and eight rehospitalizations in the 33 individuals who received the probiotics ( z = 2.63, P = .009). Hazard functions indicated that the administration of the probiotics was associated with a significant advantage in time to all psychiatric rehospitalizations (hazard ratio [HR] = 0.26, 95% confidence interval [CI] 0.10, .69; P = .007). Probiotic treatment also resulted in fewer days rehospitalized (mean 8.3 vs 2.8 days for placebo and probiotic treatment, respectively; χ 2 = 5.17, P = .017). The effect of the probiotic treatment on the prevention of rehospitalization was increased in individuals with elevated levels of systemic inflammation at baseline. Conclusion: Probiotic supplementation is associated with a lower rate of rehospitalization in patients who have been recently discharged following hospitalization for mania.